The Correlation Between CTAS Level and NEWS Score in Patients at the Emergency Department of RSUD Umar Wirahadikusumah - Safira Putri Amelia; Hikmat Pramajati; Rafika Rosyda; Ayu Prameswari Kusuma Astuti (LPPM STIKes Muhammadiyah Ciamis, 2026)
The Emergency Department (ED) requires rapid and accurate evaluation of patients’ clinical conditions to support effective triage and timely intervention. The Canadian Triage Acuity Scale (CTAS) classifies patients based on clinical urgency, while the National Early Warning Score (NEWS) assesses physiological parameters to detect early deterioration. Evidence on the relationship between these tools remains limited, particularly in Indonesia, and discrepancies between them may result in undertriage or overtriage, affecting patient safety. This study aimed to determine the relationship between CTAS levels and NEWS scores among patients in the ED of RSUD Umar Wirahadikusumah. An analytical observational study with a cross-sectional design was conducted on 307 patients selected through simple random sampling across different shifts. Data were collected using CTAS and NEWS assessment sheets and analyzed using the Spearman rank correlation test. The results showed a statistically significant but very weak positive correlation between CTAS and NEWS (r = 0.184, p < 0.001), indicating that higher CTAS levels tend to be associated with higher NEWS scores, although not consistently. The presence of undertriage and overtriage reflects inconsistencies between clinical judgment and physiological assessment. These findings suggest that CTAS and NEWS assess complementary aspects of patient acuity, and their integration may improve triage accuracy, reduce misclassification, and enhance patient safety in emergency care.